Quantification of residual stresses in electron beam welded fracture mechanics specimens. (February 2017) - Kapadia, Priyesh; Davies, Catrin; Pirling, Thilo; Hofmann, Michael; Wimpory, Robert; Hosseinzadeh, Foroogh; Dean, David; Nikbin, Kamran
Highlights: Electron beam welding is shown to produce repeatable residual stress fields in thick samples. Longitudinal stress components of up to three times the base material's yield stress were measured. The residual stresses measured by neutron diffraction, the contour method and slitting techniques are in good agreement. A correction was applied to the contour method measurements to reduce the error due to cut tip deformations. Abstract: Residual stress measurements have been made in a range of electron beam welded samples to study how the weld induced residual stresses redistributed during fabrication of compact tension, C(T), specimens. The samples were manufactured from Type 316H stainless steel in the ex-service material condition and in material which had been preconditioned by inducing 8% plastic strain. Measurements made using neutron diffraction, slitting and the contour method were generally in good agreement and showed residual stress components of up to three times the base material's yield strength existed in the samples. When sectioning a sample to perform the contour method, large elastic deformations occurred at the cut tip due to the large residual stresses present. A correction was applied to the measured surface displacements to account for this deformation. Neutron diffraction measurements were made at various stages of the fabrication process, which showed significant stress redistribution occurred as the welded samples were machined into C(T) specimens. However the tensile stresses near the crack tip of the C(T) specimens remained large and could significantly influence subsequent crack growth tests.